Pengaruh Adverse Selection dan Negative Framing pada Kecenderungan Eskalasi Komitmen - Sari, Ari Puspa; Kusuma, Gede Wira (Jurnal Ilmiah Akuntansi dan Bisnis, 2017)
Escalation of commitment is a decision to increase or expand the commitment to a project or a particular investment even though the investment project or indicate failure. This research has the objective to obtain empirical evidence of the effect of adverse selection and negative framing effect on the escalation of commitment tendency. Experimental design used of this research is 2 x 2 factorial design with the instrument in the form of cases. Participants in this research were Magister ofAccounting and Magister of Management students, as a proxy manager chosen by purposive sampling technique as much as 196 participants. This research uses of two ways ANOVA analysis techniques. This research proves that adverse selection and negative framing have an influence on the propensity of escalation of commitment.
Keywords: Adverse selection, negative framing, eskalasi komitment